Clinical efficacy and side effects of antimalarials in systemic lupus erythematosus: a systematic review. Issue 01 (22nd December 2008) - Ruiz-Irastorza, G; Ramos-Casals, M; Brito-Zeron, P; Khamashta, M A
Abstract : Background: Antimalarial drugs (AMs), chloroquine (CQ) and hydroxychloroquine (HCQ), are frequently withdrawn in patients with lupus with either severe or remitting disease. However, additional effects beyond immunomodulation have been recently described. The aim of the present work was to analyse all the published evidence of the beneficial and adverse effects of AM therapy in systemic lupus erythematosus (SLE). Methods: A systematic review of the English literature between 1982 and 2007 was conducted using the MEDLINE and EMBASE databases. Randomised controlled trials (RCTs) and observational studies were selected. Case reports were excluded except for toxicity reports. The GRADE system was used to analyse the quality of the evidence. Results: A total of 95 articles were included in the systematic review. High levels of evidence were found that AMs prevent lupus flares and increase long-term survival of patients with SLE; moderate evidence of protection against irreversible organ damage, thrombosis and bone mass loss. Toxicity related to AMs is infrequent, mild and usually reversible, with HCQ having a safer profile. In pregnant women, high levels of evidence were found that AMs, particularly HCQ, decrease lupus activity without harming the baby. By contrast, evidence supporting an effect on severe lupus activity, lipid levels and subclinical atherosclerosis was weak. Individual papers suggest effects in preventing the evolution from SLE-like to full-blown SLE, influencing vitamin D levels and protecting patients with lupus against cancer. Conclusions: Given the broad spectrum of beneficial effects and the safety profile, HCQ should be given to most patients with SLE during the whole course of the disease, irrespective of its severity, and be continued during pregnancy.